Development and evaluation of finasteride loaded ethosomes for targeting to the pilosebaceous unit. (17th November 2018) - Wilson, Vinny; Siram, Karthik; Rajendran, Selvakumar; Sankar, Veintramuthu
Abstract: Androgenetic alopecia, a major cause for baldness, is caused by the deposition of dihydrotestosterone (DHT) at the androgen receptors present in the pilosebaceous unit (PSU). Finasteride (FIN) is a potent 5α-reductase inhibitor capable of preventing the conversion of testosterone to DHT. But, its oral administration in males causes infertility. An attempt was made to prepare ethosomes of FIN with a size range 100–300 nm to enhance its delivery to the PSU. Finasteride loaded ethosomes (FES) were prepared using an ultra-probe sonicator and characterized for its size, morphology, surface charge and entrapment efficiency. The ability of FES to permeate across rat skin and frontal scalp skin of human cadaver was also evaluated. The spherical shaped ethosomes of different batches were in the size range of 107.8 ± 2.50 to 220.4 ± 6.92 nm and showed good permeation across rat skin and frontal scalp skin of human cadaver when compared to the unencapsulated FIN. The results portrayed the ability of FES to permeate across the stratum corneum to reach the PSU of the hair follicle. Although additional use of permeation enhancer increases the permeation of FIN across the skin, its addition may not be a favourable option for the deposition of ethosomes in the PSU.